Effect of Different Sources of Phosphorus on Nutrient Content and Uptake by Chickpea (Cicer arietinum L.) - Kumar, Suraj; Meena, R.H.; Singh, D.P.; Saharan, Vinod; Swami, Hemant (International Journal of Environment, Agriculture and Biotechnology, 2024)
A field experiment entitled “Effect of Different Sources of Phosphorus on Productivity of Chickpea (Cicer arietinum L.) and Soil Properties” was conducted during Rabi season of 2023-24 at Instructional Farm, Rajasthan College of Agriculture, Udaipur (Rajasthan). The experiment included nine phosphorus sources treatments (SSP, RP with and without PSB). The experiment was set up in a randomized block design with three replications. Application of 75% RDP through SSP +25% RDP through RP + PSB (T7) significantly increased nutrient content and uptake (N, P and K) by chickpea (Cicer arietinum L.) and recorded highest nutrient content and uptake over control.